A kind of gas field produced water adsorption lithium extraction adsorbent and its preparation method
Patent Information
- Application Number
- CN202510507588.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2026-10-23
AI Technical Summary
这是由于气田采出水与盐湖卤水水质差异大,相较盐湖卤水其杂质含量多,富含高盐、高硫、石油类、复杂有机物等物质,导致提锂难度变大,现有提锂吸附剂的锂回收率难以满足预期
[0030]本发明的提锂吸附剂通过锰源、锂源、支撑剂和金属助剂相互协同作用,增加锂离子吸附位点,优化吸附剂的晶体结构,改善吸附剂表面电荷,可以提升离子交换能力,使气田采出水中的锂离子与提锂吸附剂表面负电荷区域发生静电吸引,进而与提锂吸附剂中H+发生离子交换,实现了对气田采出水中锂离子的高效选择性吸附。同时,金属助剂中金属元素的引入和支撑剂的加入增强了吸附剂的结构稳定性和选择性,使其能够在含盐量更高的的气田采出水环境中保持长时间高效的吸附性能和结构稳定。综上,相较于其他盐湖卤水吸附剂,本发明的提锂吸附剂制得的提锂吸附剂具有高稳定性和高提取容量,其选择性和适应性高,能够广泛应用于气田采出水的锂提取。
Smart Images

Figure CN122955474A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas field produced water resource utilization technology, and specifically relates to a lithium adsorbent for gas field produced water and its preparation method. Background Technology
[0002] With the unprecedented development of the new energy industry, lithium metal, due to its high electrochemical activity and ultra-high energy density, is receiving increasing attention in fields such as battery materials, leading to a surge in demand for lithium resources. Produced water from gas fields is formation water discharged during oil and gas field extraction; it is abundant and rich in high-value resources such as lithium. However, current conventional treatment methods for produced water from gas fields mainly involve off-site reinjection or compliant discharge, resulting in a waste of lithium resources. Therefore, there is an urgent need to develop lithium extraction technologies suitable for produced water from gas fields.
[0003] Currently, commonly used liquid lithium extraction technologies include evaporation, solvent extraction, electrochemical methods, membrane separation, and adsorption. Among these, adsorption is a widely studied method due to its high ion selectivity, environmental friendliness, and simple process. For example, CN118807684A discloses a high-adsorption-capacity lithium extraction adsorbent from salt lakes and its preparation method. This adsorbent consists of a unique layered material composed of monovalent Li and trivalent Al, enabling selective entry of Li into the solid phase to form LiAl-LDHs. This adsorbent exhibits excellent performance in the field of lithium extraction from salt lakes. Another example is CN118949946A, which discloses a manganese-based adsorbent, its preparation method, and its application. This adsorbent consists of a crown ether single-arm resin layer coated on the surface of a cation-modified manganese ion sieve. The single-arm resin layer effectively allows lithium and hydrogen ions to pass through while hindering divalent manganese ions. The crown ether single-arm resin layer on the outside significantly mitigates the dissolution of manganese during the recycling process. However, current research indicates that most existing lithium extraction adsorbents are used for lithium extraction from salt lake brines, with very few applications in lithium extraction from gas field produced water. This is because the quality of gas field produced water differs significantly from that of salt lake brines. Gas field produced water contains more impurities and is rich in high-salt, high-sulfur, petroleum, and complex organic matter, making lithium extraction more difficult and resulting in lithium recovery rates that are insufficient to meet expectations.
[0004] Therefore, this invention proposes an adsorbent for lithium extraction from gas field produced water and its preparation method, developing an adsorbent suitable for lithium extraction from gas field produced water, improving the lithium recovery efficiency of gas field produced water, and realizing the resource utilization of gas field produced water. Summary of the Invention
[0005] To address the aforementioned technical problems, the main objective of this invention is to provide an adsorbent for lithium extraction from gas field produced water and its preparation method, thereby developing an adsorbent suitable for lithium extraction from gas field produced water, improving the lithium recovery efficiency of gas field produced water, and realizing the resource utilization of gas field produced water.
[0006] To achieve the above objectives, the present invention provides a method for preparing a lithium extraction adsorbent from produced water in gas fields, comprising the following steps:
[0007] Step S1: The manganese source, lithium source and metal additive are subjected to a hydrothermal reaction to obtain the reaction product;
[0008] Step S2: The reacted material is dried and calcined sequentially to obtain the precursor of the adsorption active material;
[0009] Step S3: Add an oxidant to the precursor of the adsorbent active material, and wash and dry it sequentially to obtain the adsorbent active material.
[0010] Step S4: The adsorbent active material is mixed and ground with the support and binder to obtain a ground mixture;
[0011] Step S5: The grinding mixture is subjected to a mixing and molding process to obtain the gas field produced water adsorbent for lithium extraction.
[0012] Furthermore, the manganese source is selected from any one of Mn2O3, Mn3O4, MnO, MnOOH or (CH3COO)2Mn.
[0013] Furthermore, the lithium source is selected from any one of LiOH, LiNO3, LiCl, or CH3COOLi.
[0014] Furthermore, the metal additive is selected from one or two of iron salts, aluminum salts, or magnesium salts.
[0015] Furthermore, the molar ratio of manganese in the manganese source to lithium in the lithium source is 1:1 to 4:1.
[0016] Furthermore, the molar ratio of manganese in the manganese source to lithium in the lithium source is 15:1 to 20:1.
[0017] Furthermore, the metal additive is selected from one or two of Fe(OH)(CH3COO)2, AlCl3, or Mg(NO3)2.
[0018] Furthermore, the oxidant is selected from hydrochloric acid and / or sulfuric acid.
[0019] Furthermore, the liquid-solid mass ratio of the oxidant to the adsorption active material precursor is 300-500:1.
[0020] Furthermore, the proppant is selected from one or more of carbon fiber powder, carbon nanotubes, or powdered activated carbon.
[0021] Furthermore, the adhesive is selected from one or more of cellulose acetate, sodium alginate, polystyrene, or polyvinyl chloride.
[0022] Furthermore, in the grinding mixture, based on 100 parts by weight, the adsorbent active material is 85-95 parts, the support is 2-7 parts, and the binder is 3-12 parts.
[0023] Furthermore, the hydrothermal reaction is carried out at a temperature of 120–180°C for a duration of 8–12 hours.
[0024] Furthermore, the pH value of the hydrothermal reaction is 9–11.
[0025] Furthermore, the drying process is carried out at a temperature of 85–95°C for 6–12 hours.
[0026] Furthermore, the calcination temperature is 450–650°C, and the time is 4–6 hours.
[0027] Furthermore, the roasting atmosphere is nitrogen or air.
[0028] In another aspect, the present invention provides a lithium extraction adsorbent for gas field produced water, which is prepared by the aforementioned method for preparing the lithium extraction adsorbent for gas field produced water.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The lithium extraction adsorbent of this invention utilizes the synergistic effect of a manganese source, a lithium source, a proppant, and a metal additive to increase lithium ion adsorption sites, optimize the crystal structure of the adsorbent, and improve the surface charge of the adsorbent. This enhances the ion exchange capacity, enabling electrostatic attraction between lithium ions in gas field produced water and the negatively charged regions on the surface of the lithium extraction adsorbent, thereby facilitating the exchange of lithium ions with H+ in the adsorbent. + Ion exchange occurs, achieving highly efficient and selective adsorption of lithium ions in gas field produced water. Simultaneously, the introduction of metal elements in the metal additive and the addition of a proppant enhance the structural stability and selectivity of the adsorbent, enabling it to maintain high adsorption performance and structural stability for extended periods in gas field produced water environments with higher salinity. In summary, compared to other brine adsorbents, the lithium extraction adsorbent prepared by this invention exhibits high stability and high extraction capacity, as well as high selectivity and adaptability, making it widely applicable for lithium extraction from gas field produced water. Attached Figure Description
[0031] Figure 1 A schematic flowchart of a method for preparing a lithium extraction adsorbent from gas field produced water according to one embodiment of the present invention is shown.
[0032] Figure 2 The crystal structure characterization diagrams of the adsorption active material precursors prepared in Examples 1 to 4 of the present invention are shown. Detailed Implementation
[0033] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range. The invention will now be described in detail with reference to embodiments.
[0034] To achieve the above objectives, a first aspect of the present invention provides a method for preparing a lithium extraction adsorbent from produced water in a gas field, such as... Figure 1 As shown, it includes the following steps:
[0035] Step S1: The manganese source, lithium source and metal additive are subjected to a hydrothermal reaction to obtain the reaction product;
[0036] Step S2: The reacted material is dried and calcined sequentially to obtain the precursor of the adsorption active material;
[0037] Step S3: Add an oxidant to the precursor of the adsorbent active material, and wash and dry it sequentially to obtain the adsorbent active material.
[0038] Step S4: The adsorbent active material is mixed and ground with the support and binder to obtain a ground mixture;
[0039] Step S5: The grinding mixture is subjected to a mixing and molding process to obtain the gas field produced water adsorbent for lithium extraction.
[0040] The lithium extraction adsorbent of this invention utilizes the synergistic effect of a manganese source, a lithium source, a proppant, and a metal additive to increase lithium ion adsorption sites, optimize the crystal structure of the adsorbent, and improve the surface charge of the adsorbent. This enhances the ion exchange capacity, enabling electrostatic attraction between lithium ions in gas field produced water and the negatively charged regions on the surface of the lithium extraction adsorbent, thereby facilitating the exchange of lithium ions with H+ in the adsorbent. + Ion exchange occurs, achieving highly efficient and selective adsorption of lithium ions in gas field produced water. Simultaneously, the introduction of metal elements into the metal additive and the addition of a proppant enhance the structural stability and selectivity of the adsorbent, enabling it to maintain high adsorption performance and structural stability for extended periods in gas field produced water environments with higher salinity. Compared to other brine adsorbents, the adsorbent of this invention exhibits higher selectivity and adaptability, and can be widely applied to lithium extraction from gas field produced water.
[0041] In some preferred embodiments of the present invention, the manganese source is selected from any one of Mn2O3, Mn3O4, MnO, MnOOH, or (CH3COO)2Mn. The lithium source is selected from any one of LiOH, LiNO3, LiCl, or CH3COOLi.
[0042] In a preferred embodiment of the present invention, the metal additive is selected from one or two of iron salts, aluminum salts, or magnesium salts. Iron salts, aluminum salts, or magnesium salts generally have lower toxicity and are more inexpensive, which can significantly reduce the overall preparation cost of the adsorbent and make them more suitable for large-scale industrial production.
[0043] More preferably, the metal additive is selected from one or two of Fe(OH)(CH3COO)2, AlCl3, or Mg(NO3)2. Using the aforementioned metal additive makes it easier to dissolve and disperse during the preparation of the lithium extraction adsorbent, enabling uniform doping and the formation of a more stable composite oxide structure, thereby further improving the lithium extraction effect of the lithium extraction adsorbent.
[0044] In a preferred embodiment of the present invention, the molar ratio of manganese in the manganese source to lithium in the lithium source is 1:1 to 4:1. For example, it can be selected from 1:1, 1.25:1, 1.5:1, 1.75:1, 2:1, 2.5:1, 2.75:1, 3:1, 3.5:1, and 4:1. If the molar ratio of manganese in the manganese source to lithium in the lithium source is not within the above range, both excessively high and excessively low mass ratios will lead to a decrease in adsorption capacity, a decrease in the structural stability of the adsorbent, and an increase in the adsorption of competing ions (such as sodium, potassium, magnesium, calcium, etc.).
[0045] In a preferred embodiment of the present invention, the molar ratio of manganese in the manganese source to the metal element in the metal additive is 15:1 to 20:1. For example, it can be selected from 15:1, 15.5:1, 16:1, 16.5:1, 17:1, 17.5:1, 18:1, 18.5:1, 19:1, 19.5:1, and 20:1. If the ratio of manganese in the manganese source to the metal element in the metal additive is not within the above-mentioned range, the content of the doped metal element is too low, which cannot effectively stabilize the spinel crystal structure of MO and increase the surface negative charge density, thus failing to fully utilize the synergistic effect of the doped metal, leading to a decrease in adsorption rate and structural stability. Conversely, an excessively high content of the doped metal element may occupy lithium-ion intercalation sites in the manganese oxide, also resulting in a decrease in adsorption capacity.
[0046] In some preferred embodiments of the present invention, the oxidant is selected from hydrochloric acid and / or sulfuric acid. The liquid-solid mass ratio of the oxidant to the precursor of the adsorption active material is 300-500:1. The molar concentration of the oxidant is 0.05-0.2 mol / L. The washing time for the oxidant is 4-8 h. In the preparation process of the lithium extraction adsorbent of the present invention, the addition of an oxidant can activate a large number of lithium ion adsorption sites. Controlling the concentration and amount of the oxidant within the above-mentioned range can effectively improve the performance of the lithium extraction adsorbent. If the amount or concentration of the oxidant is too high, it will lead to structural damage to the lithium extraction adsorbent, loss of active sites, and increased cost. If the conditions are too low, the activation effect is not obvious and the improvement in adsorption performance is limited.
[0047] In a preferred embodiment of the present invention, the support agent is selected from one or more of carbon fiber powder, carbon nanotubes, or powdered activated carbon. The present invention innovatively incorporates a carbon-containing support material during the lithium extraction adsorbent process. This material has a high specific surface area and high strength, which can more effectively increase the specific surface area and lithium ion adsorption sites of the lithium extraction adsorbent, while also enhancing the mechanical strength and structural stability of the lithium extraction adsorbent and improving its recyclability.
[0048] In a preferred embodiment of the present invention, the adhesive is selected from one or more of cellulose acetate, sodium alginate, polystyrene, or polyvinyl chloride.
[0049] In a preferred embodiment of the present invention, the grinding mixture comprises, by weight 100 parts, 85-95 parts of adsorbent active material, 2-7 parts of support, and 3-12 parts of binder. The present invention further controls the weight ratio of adsorbent active material, support, and binder, effectively increasing the mechanical strength and stability of the lithium-extraction adsorbent while maintaining high lithium extraction adsorption efficiency, thereby improving the recyclability of the adsorbent.
[0050] In some preferred embodiments of the present invention, the temperature of the hydrothermal reaction is 120–180°C, for example, selected from 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, and 180°C. The time is 8–12 hours, for example, selected from 8 hours, 9 hours, 10 hours, 11 hours, and 12 hours. The pH value of the hydrothermal reaction is 9–11, for example, selected from 9, 9.5, 10, 10.5, and 11. By controlling the hydrothermal reaction conditions within the above range, the present invention can effectively control the crystal structure and morphology, achieve uniform doping, and enhance the crystallinity and structural stability of the adsorbent.
[0051] In some preferred embodiments of the present invention, the drying treatment is performed at a temperature of 85–95°C for 6–12 hours. The calcination temperature is 450–650°C for 4–6 hours. The calcination atmosphere is nitrogen or air. The mixture forming process is extrusion molding.
[0052] In a second aspect, the present invention also provides a lithium adsorbent for adsorbing produced water from gas fields, which is prepared by the aforementioned method for preparing lithium adsorbents for adsorbing produced water from gas fields.
[0053] Based on the reasons mentioned above, the lithium adsorbent for adsorbing produced water from gas fields prepared by this invention has excellent lithium-ion adsorption efficiency and structural stability, and can be well applied to the process of adsorbing and extracting lithium from produced water from gas fields, realizing the resource utilization of produced water from gas fields.
[0054] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.
[0055] Example 1
[0056] An adsorbent for lithium extraction from produced water in gas fields is prepared by the following method, which includes the following steps:
[0057] (1) Mn2O3, LiNO3 and AlCl3 were added to a hydrothermal reactor in a molar ratio of 10:20:1 and the hydrothermal reaction was carried out at pH=11 and 120℃ for 8 hours to obtain the reaction material;
[0058] (2) The reacted material was dried in a drying oven at 95°C for 8 hours, and then the dried powder was calcined in a tube furnace at 450°C in air atmosphere for 6 hours to obtain the precursor of the adsorption active material; the crystal structure of the precursor of the adsorption active material is characterized as follows: Figure 2 As shown;
[0059] (3) The precursor of the adsorption active material was washed with 0.1 mol / L hydrochloric acid solution at a liquid-solid mass ratio of 400:1 for 8 hours, and then dried in a drying oven to obtain the adsorbent active material.
[0060] (4) The adsorbent active material is mixed and ground with carbon fiber powder and cellulose acetate in a weight ratio of 85%:3%:12% to obtain a grinding mixture;
[0061] (5) The grinding mixture is briquetting into balls by a briquetting machine to obtain a lithium adsorbent for adsorbing produced water from the gas field.
[0062] Example 2
[0063] An adsorbent for lithium extraction from produced water in gas fields is prepared by the following method, which includes the following steps:
[0064] (1) (CH3COO)2Mn, CH3COOLi and Fe(OH)(CH3COO)2 were mixed in a molar ratio of 15:15:1 and the pH was adjusted to 9. The mixture was subjected to a hydrothermal reaction at 180℃ for 12 hours to obtain the reaction product.
[0065] (2) The reacted material was dried in a drying oven at 85°C for 6 hours, and then the dried powder was calcined in a tube furnace at 650°C for 4 hours under a nitrogen atmosphere to obtain the precursor of the adsorption active material; the crystal structure of the precursor of the adsorption active material is characterized as follows: Figure 2 As shown;
[0066] (3) The precursor of the adsorption active material was washed with 0.05 mol / L sulfuric acid solution at a liquid-solid mass ratio of 500:1 for 6 hours, and then dried in a drying oven to obtain the adsorbent active material.
[0067] (4) The adsorbent active material, powdered activated carbon, and polystyrene are thoroughly mixed and ground in a weight ratio of 90%:3%:7% to obtain a grinding mixture;
[0068] (5) The grinding mixture is briquetting into balls by a briquetting machine to obtain a lithium adsorbent for adsorbing produced water from the gas field.
[0069] Example 3
[0070] An adsorbent for lithium extraction from produced water in gas fields is prepared by the following method, which includes the following steps:
[0071] (1) MnOOH, LiNO3 and Mg(NO3)2 were added to a hydrothermal reactor in a molar ratio of 15:15:1, and the hydrothermal reaction was carried out for 10 hours at pH=10 and 150℃ to obtain the reaction material.
[0072] (2) The reacted material was dried in a drying oven at 90°C for 12 hours, and then the dried powder was calcined in a tube furnace at 550°C in an air atmosphere for 5 hours to obtain the precursor of the adsorption active material; the crystal structure of the precursor of the adsorption active material is characterized as follows: Figure 2 As shown;
[0073] (3) The precursor of the adsorption active material was washed with 0.2 mol / L hydrochloric acid solution at a liquid-solid mass ratio of 300:1 for 8 hours, and then dried in a drying oven to obtain the adsorbent active material.
[0074] (4) The adsorbent active material, carbon nanotubes, and polyvinyl chloride are mixed and ground in a weight ratio of 91%:3%:6% to obtain a grinding mixture;
[0075] (5) The grinding mixture is briquetting into balls by a briquetting machine to obtain a lithium adsorbent for adsorbing produced water from the gas field.
[0076] Example 4
[0077] An adsorbent for lithium extraction from produced water in gas fields is prepared by the following method, which includes the following steps:
[0078] (1) MnCO3, Li2CO3 and Mg(NO3)2 were added to a hydrothermal reactor in a molar ratio of 20:5:1. The hydrothermal reaction was carried out at pH=9 and 140℃ for 8 hours to obtain the reaction product.
[0079] (2) The reacted material was dried in a drying oven at 95°C for 6 hours, and then the dried powder was calcined in a tube furnace at 500°C in an air atmosphere for 6 hours to obtain the precursor of the adsorption active material; the crystal structure of the precursor of the adsorption active material is characterized as follows: Figure 2 As shown;
[0080] (3) The precursor of the adsorption active material was washed with 0.1 mol / L sulfuric acid solution at a liquid-solid mass ratio of 400:1 for 4 hours, and then dried in a drying oven to obtain the adsorbent active material.
[0081] (4) The adsorbent active material, carbon fiber powder, and sodium alginate are mixed and ground in a weight ratio of 94%:3%:3% to obtain a grinding mixture;
[0082] (5) The grinding mixture is briquetting into balls by a briquetting machine to obtain a lithium adsorbent for adsorbing produced water from the gas field.
[0083] Example 5
[0084] A lithium extraction adsorbent for gas field produced water is prepared in a manner that differs from that in Example 1 in that the molar ratio of manganese in the manganese source to lithium in the lithium source and the metal element in the metal additive is 10:5:1.
[0085] Example 6
[0086] A lithium extraction adsorbent for gas field produced water is prepared in a manner that differs from that in Example 1 in that the metal additive is aluminum nitrate.
[0087] Example 7
[0088] A lithium extraction adsorbent for gas field produced water is prepared in a manner that differs from that in Example 2 in that the metal additive is ferric nitrate.
[0089] Comparative Example 1
[0090] A lithium extraction adsorbent for gas field produced water is prepared in a manner that differs from that in Example 1 in that the molar ratio of manganese in the manganese source to lithium in the lithium source and the metal element in the metal additive is 15:30:1.
[0091] Comparative Example 2
[0092] A lithium extraction adsorbent for gas field produced water is prepared in a manner that differs from that in Example 1 in that the molar ratio of manganese in the manganese source to lithium in the lithium source and the metal element in the metal additive is 5:10:1.
[0093] Comparative Example 3
[0094] A lithium extraction adsorbent for gas field produced water is prepared in a manner that differs from that in Example 1, wherein the grinding mixture contains, by weight, 85 parts of active material, 10 parts of proppant, and 5 parts of binder.
[0095] Comparative Example 4
[0096] A lithium-extraction adsorbent for gas field produced water is prepared in a way that differs from that in Example 1 only in that no metal additives are added to its raw materials. Mn2O3 and LiNO3 are added to a hydrothermal reactor in a molar ratio of 10:20 for reaction.
[0097] Comparative Example 5
[0098] A lithium extraction adsorbent for gas field produced water is prepared in a manner that differs from that in Example 1 only in that no support agent is added to the raw materials, and the weight ratio of the active material to the binder is 85% and 15%.
[0099] The lithium extraction adsorbents from the gas field produced water in the above examples and comparative examples were placed in an adsorption column for lithium extraction from the produced water. The produced water came from a processing station of an oil and gas field in Xinjiang. The water quality analysis is shown in Table 1 (the lithium content of the water fluctuated slightly in each experiment). After an adsorption time of 8 hours, the lithium ion adsorption efficiency and manganese dissolution rate were tested (the stability of the adsorbent was judged by the manganese dissolution rate, and the lower the manganese dissolution rate, the higher the stability). The test data are shown in Table 2.
[0100] Table 1. Analysis of produced water quality
[0101]
[0102] Table 2 Lithium ion adsorption rate and manganese dissolution rate
[0103]
[0104]
[0105] As can be seen from Table 2, the lithium ion adsorption rate of the lithium extraction adsorbent for gas field produced water in the embodiments of the present invention is higher than 84%, and the manganese dissolution rate is lower than 0.9%, indicating that the lithium extraction adsorbent of the present invention has both excellent lithium ion adsorption rate and recycling performance.
[0106] A comparison of Example 1 and Comparative Examples 1 and 2 revealed that the lithium-ion adsorption rate decreased and the manganese dissolution rate increased in Comparative Examples 1 and 2. This is because the content of the doped metal element in Comparative Example 1 was too low, which prevented it from effectively stabilizing the spinel crystal structure of MO and increasing the surface negative charge density, thus failing to fully utilize the synergistic effect of the doped metal, resulting in a decrease in lithium-ion adsorption efficiency and stability. In contrast, the content of the doped metal element in Comparative Example 2 was too high, occupying lithium-ion intercalation sites in the manganese oxide, leading to a decrease in adsorption capacity and a decrease in manganese dissolution rate.
[0107] Through Example 1 and Comparative Example 4, it can be found that the manganese dissolution rate and adsorption efficiency of the lithium extraction adsorbent in Comparative Example 4, which did not add metal additives, decreased significantly. This is because the lack of synergistic effect between metal elements and manganese elements led to a significant reduction in the structural stability and selectivity of the adsorbent.
[0108] Through Example 1 and Comparative Examples 3 and 5, it can be found that by reasonably controlling the weight ratio of the active material, support and binder of the adsorbent, the mechanical strength and stability of the lithium adsorbent can be effectively increased while maintaining the high lithium extraction adsorption efficiency, and the manganese dissolution rate can be reduced, thereby improving the recyclability of the adsorbent.
[0109] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing an adsorbent for lithium extraction from produced water in a gas field, characterized in that, Includes the following steps: Step S1: The manganese source, lithium source and metal additive are subjected to a hydrothermal reaction to obtain the reaction product; Step S2: The reacted material is dried and calcined sequentially to obtain the precursor of the adsorption active material; Step S3: Add an oxidant to the precursor of the adsorbent active material, and wash and dry it sequentially to obtain the adsorbent active material. Step S4: The adsorbent active material is mixed and ground with the support and binder to obtain a ground mixture; Step S5: The grinding mixture is subjected to a mixing and molding process to obtain the gas field produced water adsorbent for lithium extraction.
2. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The manganese source is selected from any one of Mn2O3, Mn3O4, MnO, MnOOH or (CH3COO)2Mn.
3. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The lithium source is selected from any one of LiOH, LiNO3, LiCl or CH3COOLi.
4. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The metal additive is selected from one or two of iron salts, aluminum salts, or magnesium salts.
5. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The molar ratio of manganese in the manganese source to lithium in the lithium source is 1:1 to 4:
1. And / or, the molar ratio of manganese in the manganese source to metal in the metal additive is 15:1 to 20:
1.
6. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 4, characterized in that, The metal additive is selected from one or two of Fe(OH)(CH3COO)2, AlCl3, or Mg(NO3)2.
7. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The oxidant is selected from hydrochloric acid and / or sulfuric acid.
8. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1 or 7, characterized in that, The liquid-solid mass ratio of the oxidant to the adsorption active material precursor is 300-500:
1.
9. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The proppant is selected from one or more of carbon fiber powder, carbon nanotubes, or powdered activated carbon.
10. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The adhesive is selected from one or more of cellulose acetate, sodium alginate, polystyrene, or polyvinyl chloride.
11. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, In the grinding mixture, based on 100 parts by weight, the adsorbent active material is 85-95 parts, the support is 2-7 parts, and the binder is 3-12 parts.
12. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 120–180°C for 8–12 hours. And / or, the pH value of the hydrothermal reaction is 9 to 11.
13. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The drying process is carried out at a temperature of 85–95°C for 6–12 hours.
14. The preparation method of the lithium extraction adsorbent from gas field produced water according to claim 1, characterized in that, The roasting temperature is 450–650℃, and the time is 4–6 hours; And / or, the roasting atmosphere is nitrogen or air.
15. A lithium extraction adsorbent for gas field produced water, characterized in that, It is prepared by the method of any one of claims 1 to 14 for the preparation of lithium extraction adsorbent from gas field produced water.